A Diabetes Self-Management Education/Support (DSME/S) Program in Reference to the Biological, Psychological and Social Aspects of a Patient with Type 2 Diabetes Mellitus: A Systematic Review - Novita Fajriyah; Tria Anisa Firmanti; Ainul Mufidah; Nita Tri Septiana (Jurnal Ners, 2019)
Introduction: Various efforts have been made to improve the self-care management of patients with type 2 diabetes mellitus (T2DM). One of them is by using a Diabetes Self-Management Education and Support (DSME/S) program. DSME/S produces positive effects in relation to patient behavior and health status. This is a systematic review of randomized controlled trials published where the aim was to evaluate the impact of the DSME/S program in term of biological. psychological and social aspects.Methods: The articles were searched for using the PRISMA approach from within Scopus, Sage Journal, ProQuest, Google Scholar and PubMed to identify the relevant English publications on DSME over the last 5 years (2013-2018). In total, 15 studies met the inclusion criteria.Results: The articles included at least one result that covered the biological, psychological, and social aspects that are more general and relevant for T2DM patients who received the DSME program. DSME had a positive impact on T2DM, namely the reduction of HbA1c, blood glucose, LDL, cholesterol, blood pressure, weight, waist circumference, decreased distress, anxiety and increased self-efficacy and self-empowerment.Conclusion: It can increase the social and family support, improve self-management motivation, increase knowledge and improve the behavior of T2DM patients. The findings of our review showed that DSME has a positive impact on the biological, psychological and social aspects of type 2 diabetes mellitus.